HUBUNGAN KADAR GULA DARAH SAAT MASUK RUMAH SAKIT DENGANCARDIAC EVENTS PADA PENDERITA INFARK MIOKARD AKUT DI RS DR SARDJITO YOGYAKARTA - Irawan, Bambang; Suharno, Suharno; Rochmah, Wasilah (Fakultas Kedokteran Universitas Brawijaya, 2005)
Hyperglycaemia is common in patients with acute myocardial infarction with and without diabetes mellitus. There is a positive relationship between hyperglycaemia at thetime of event and highly incidence of mortality and morbidity after acute myocardial infarction. Consequently, understanding the possible mechanisms through which hyperglycaemia worsens the prognosis of acute myocardial infarction, as well as effectiveness of its control during acute myocardial infarction, seems to be a great relevance. This study to investigate wether a relationship exists between blood glucose level on admission and cardiac events in non diabetic patients after an acute myocardial infarction. Method, a cohort prospective observational study was done on acute myocardial infarction’s patients who were hospitalized in ICCU DR Sardjito’s hospital from March 2002 until October 2004. Subject who met inclusion and exclusion criteria were divided into 2 groups, the group in which blood glucose level onadmission was ≤ 140 mg/dl and the group with bloodglucose on admission was > 140 mg/dl. Cardiac events as well as mortality, cardiac failure, reinfarction and cardiogenic shock were observed for 6 months. There were 95 subjects, 93 males and 2 females.